Are children who play a sport or a musical instrument better at motor imagery than children who do not?. Issue 13 (4th January 2012) - Dey, Abhishikta; Barnsley, Nadia; Mohan, Rahul; McCormick, Marianne; McAuley, James H; Moseley, G Lorimer
Abstract : Objective: Playing a sport or a musical instrument is presumed to improve motor ability. One would therefore predict that children who play a sport or music are better at motor imagery tasks, which rely on an intact cortical proprioceptive representation and precise motor planning, than children who do not. The authors tested this prediction. Methods: This study involved an online questionnaire and then a motor imagery task. The task measured the reaction time (RT) and the accuracy for left/right-hand judgements in children aged 5 to 17 years. Forty pictured hands (20 left), held in various positions and rotated zero, 90°, 180° or 270°, were displayed on a screen. Participants indicated whether the displayed hands were left or right by pressing keys on a keyboard. Results: Fifty-seven children (30 boys; mean±SD age=10±3.3 years) participated. The mean±SD RT was 3015.4±1330.0 ms and the accuracy was 73.9±16.6%. There was no difference in RT between children who played sport, music, neither or both (four-level one-way analysis of variance, p=0.85). There was no difference in accuracy between groups either (Kruskal–Wallis, p=0.46). In a secondary analysis, participants whose parents rated them as being 'clumsy' were no slower (n.s.) but were about 25% less accurate than those rated coordinated or very coordinated (p<0.05). Conclusion: The authors conclude against the intuitively sensible and widely held view that participation in a sport or music is associated with better cortical proprioceptive representation and motor planning. Secondary analyses suggest that parent-rated clumsiness is negatively related to motor imagery performance.